IMPLEMENTASI DANA KOMITE SEKOLAH, BOSNAS DAN BOSDA TERHADAP PENINGKATAN MUTU PENDIDIKAN (Fakultas Ekonomi dan Bisnis Universitas Faletehan, 2024)
The aim of this research is to determine the impact of implementing the School Committee Fund Policy, National School Assistance Funds (BOSNAS), and Regional School Assistance Funds (BOSDA) on improving the quality of education. The data used in this research are primary data and secondary data. This means that data is obtained directly from the source by respondents who complete the survey. The analysis techniques used are plausibility, reliability, classical assumptions, hypotheses, and multiple linear regression. Based on the results of the analysis, it can be concluded that the implementation of school committee funding policies, School Operational Assistance Funds (BOSNAS), and Regional School Operational Assistance Funds (BOSDA) will have an important plus value at the same time. time. The effect of improving the quality of education and some of each dependent variable has a significant positive effect on improving the quality of education. Therefore, in order to improve the quality of education at SMAN 10 Bandarlampung, the School Committee Fund Policy guidelines, National School Assistance Funds (BOSNAS) and Regional School Assistance Funds (BOSDA) must be considered or obeyed. in accordance with statutory regulations;